Arrhythmias in women : diagnosis and management - Cha, Yong-Mei; Lloyd, Margaret A.; Birgersdotter-Green, Ulrika M. ([Oxford] : Oxford University Press, 2014)
This title draws upon the experience of national leaders in the field of women's heart disease to address the unique aspects involved in the diagnosis and treatment of women with arrhythmias and implantable device therapy. Written by distinguished consultants in the Division of Cardiovascular Diseases of Mayo Clinic, this book provides a concise and up-to-date review of the diagnosis and treatment of atrial and ventricular arrhythmias in women.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Arrhythmia -- Diagnosis; Arrhythmia -- Treatment; Heart diseases in women